Effects of chlorhexidine varnish on caries during orthodontic treatment: a systematic review and meta-analysis - Elaine Machado Pingueiro OKADA; Larissa Nogueira Soares RIBEIRO; Maria Bernadete Sasso STUANI; Maria Cristina BORSATTO; Tatiana Kelly da Silva FIDALGO; Francisco Wanderley Garcia de PAULA-SILVA; Erika Calvano KÜCHLER
Abstract This study aimed to perform a systematic review and meta-analysis to evaluate the effectiveness of chlorhexidine varnish on the reduction of caries incidence during fixed orthodontic treatment. The literature searches involved The Cochrane Library, Medline, Scopus, OpenSigle databases and manual searches. The search on OpenSigle did not produce any additional articles. Clinical studies conducted in patients with orthodontic fixed appliances that used professional application of chlorhexidine varnish were included. The effect-size was calculated and a meta-analysis was performed. From 182 abstracts, a total of six articles fulfilled the inclusion criteria. After reading the full articles, one was excluded because of lack of a control group. Three articles were used for continuous data analysis, and two articles were used for the dichotomous data analysis. The pooled meta-analysis with continuous data demonstrated chlorhexidine varnish effectiveness on caries reduction (p = 0.003), with a mean difference and confidence interval of −1.49 [−2.47, −0.51]. On the basis of the pooled meta-analysis of continuous data, we were able to conclude that professional application of chlorhexidine varnish is effective in caries incidence reduction during fixed orthodontic treatment.